Association of N-acetylcysteine use with contrast-induced nephropathy: an umbrella review of meta-analyses of randomized clinical trials - Zhu, Rong; Zheng, Rong; Deng, Bing; Liu, Ping; Wang, Yiru (Frontiers in Medicine, 2023)
Background: The effectiveness of N-acetylcysteine (NAC) in treating contrast-induced nephropathy (CIN) has been the subject of conflicting meta-analyses, but the strength of the evidence for these correlations between NAC use and CIN has not been measured overall. Objective: To evaluate the data from randomized clinical studies (RCTs) that examined the relationships between NAC use and CIN in meta-analyses. Methods: Between the creation of the database and April 2023, searches were made in PubMed, Cochrane Library, EMBASE, and Web of Science. N-acetylcysteine, contrast-induced nephropathy, or contrast-induced renal disease were among the search keywords used, along with terms including systematic review and meta-analysis. The Assessment of Multiple Systematic Reviews, version 2, which assigned grades of extremely low, low, moderate, or high quality to each meta-analysis's scientific quality, was used to evaluate each meta-analysis. The confidence of the evidence in meta-analyses of RCTs was evaluated using the Grading of Recommendation, Assessment, Development and Evaluations method, with evidence being rated as very low, low, moderate, or high. Results: In total, 493 records were screened; of those, 46 full-text articles were assessed for eligibility, and 12 articles were selected for evidence synthesis as a result of the screening process. Based on the pooled data, which was graded as moderate-quality evidence, it can be concluded that NAC can decrease CIN (OR 0.72, 95% CI 0.65 to 0.79, P < 0.00001) and blood levels of serum creatinine (MD -0.09, 95% CI -0.17 to -0.01, P = 0.03). In spite of this, there were no associations between NAC and dialysis requirement or mortality in these studies. Conclusions: The results of this umbrella review supported that the renal results were enhanced by NAC. The association was supported by moderate-quality evidence.